2016
DOI: 10.5812/aapm.36812
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac Suppository vs. IV Acetaminophen Combined With IV PCA for Postoperative Pain Management in Patients Undergoing Laminectomy: A Randomized, Double-Blinded Clinical Trial

Abstract: BackgroundTissue damage caused by surgical procedures nearly always results in pain. The effective management of postoperative pain remains a challenge because of its influence on the surgical outcome and its critical role in early mobilization and functionality. Recent research on postoperative pain management supports a treatment approach known as “multimodal analgesia,” which comprises the use of more than one method or modality of pain control and management.ObjectivesIn the present study, we compared the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…However, the opioid-sparing effects of paracetamol are well described, and for this reason, paracetamol is also recommended for lumbar laminectomy. Furthermore, both Kesimci et al and Nikosereth et al reported no significant difference in post-operative pain scores between NSAIDs and paracetamol [12,16].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the opioid-sparing effects of paracetamol are well described, and for this reason, paracetamol is also recommended for lumbar laminectomy. Furthermore, both Kesimci et al and Nikosereth et al reported no significant difference in post-operative pain scores between NSAIDs and paracetamol [12,16].…”
Section: Discussionmentioning
confidence: 94%
“…Nikooseresh et al compared diclofenac 100 mg suppository to IV paracetamol 1000 mg [16]. Rescue analgesia included IV-PCA fentanyl.…”
Section: Systemic Analgesic Interventionsmentioning
confidence: 99%